The Controversy about the Conclusion of the Transatlantic Trade and Investment Partnership (TTIP) in a Legal Context - Schewe, Christoph (Journal of the University of Latvia. Law, 2015)
The negotiations of the Transatlantic Trade and Investment Partnership (TTIP) between the European Union (EU) and the United States have triggered considerable controversies in the EU member states about its potential impact. Civil society and the media intensely discussed substantive and procedural elements, while different groups initiated protests and even started European citizens’ initiative against this trade agreement. This article aims at giving an insight into this controversy, while also illustrating the impact of a trade agreement concluded by the EU on the member states and their citizens. The focus is directed at the negotiation process and the questions regarding the EU’s competences with regard to concluding the TTIP under the Common Commercial Policy.